A PLAUSIBLE ENERGY YIELD FROM PALM OIL MILL EFFLUENT - Cundr, Ing. OndÃ…Â™ej (Mesin, 2004)
Application of biogas generated from palm oil mill effluent for producing electricity has been proven as an ecological alternative to naphtha and fossil fuels. In the first part of this article, the process of making oil from fresh fruit bunches is briefly described together with amounts of waste gained. After that, different types of treatment of palm oil mill effluent (POME) as one of results of the process are examined, resulting in a suggestion of anaerobic digestion under thermophilic conditions as the best way to treat POME. Finally, attention is also paid to the emission reduction during an anaerobic digestion in close tanks. The aim of the article is to stress the overwhelming energy potential of POME that can bring high increase in electrification ratio and recognizable decrease of air pollution on the island of Sumatra.